THE The Relationship Between Hemoglobin Levels of Pregnant Mothers and Low Birth Weight at Dr. Moewardi Regional Hospital Surakarta - Fikritama, Aisya; Liandoro, Otniel; Sekarhandini, Pitra; Vidya, Pridania (Journal of Maternal and Child Health, 2024)
Background: Anemia is one of the nutritional problems commonly encountered in pregnant women. The World Health Organization (WHO) states that approximately 37% of pregnant women worldwide experience anemia. This condition reduces the amount of oxygen and nutrient supply available in the mother's blood, which can disrupt the development and growth of the fetus. The growth disturbances in the fetus can be evaluated through anthropometric examinations, such as measuring the birth weight of the baby. This study aims to determine the relationship between hemoglobin levels in pregnant women and the incidence of low birth weight. Subjects and Method: A cross-sectional study was conducted at Dr. Moewardi Regional Hospital in Surakarta from May to July 2024. A total of 68 pragnant women selected for this study. The dependent variable was newborn baby weight. The independent variable was hemoglobin levels of pregnant women in the third trimester. The data obtained from patient medical records. The data analyzed using a multiple logistic regression.    Results: Low Hb levels (anemia) increase the incidence of LBW. Pregnant women with low Hb levels (anemia) have a 2.30 times greater risk of experiencing LBW compared to pregnant women with normal HB levels, but this result was not statistically significant (OR= 2.30; 95% CI = 0.14 to 38.63; p = 0.563). Conclusion: Low Hb levels increase the incidence of LBW, but it is not statistically.